Strengthening Regional Disaster Management Governance through a Risk-Based Policy Framework - Dede Mirza; Erinaldi Erinaldi; Wafa Adilla (International Journal of Social Welfare and Family Law, 2024)
This study examines the strengthening of regional disaster management governance through a risk-based policy framework, focusing on the role of local governments in disaster-prone areas. The object of the study is the disaster management system implemented by the Dumai City Regional Disaster Management Agency (BPBD), which faces various potential natural and non-natural disasters. Although national and regional regulatory frameworks are in place, disaster management practices at the regional level still tend to be reactive, partial, and not fully based on comprehensive risk analysis. Therefore, this study aims to identify key issues in regional disaster management governance and analyze the role of risk-based policies in strengthening institutional effectiveness, cross-sectoral coordination, and disaster preparedness. This study uses a qualitative descriptive approach with data collection techniques through in-depth interviews with BPBD officials, relevant stakeholders, and community representatives in disaster-prone areas, supported by field observations and documentation studies of policies, disaster risk assessment documents, and institutional reports. Data analysis was conducted using thematic analysis methods to identify patterns related to governance structures, policy implementation, and disaster risk management practices. The study results indicate that disaster management governance in Dumai City has shown progress in regulatory aspects and emergency response capacity, but there are still weaknesses in the integration of risk into development planning, inter-agency coordination, community participation, and mitigation and prevention efforts. This study concludes that the implementation of a risk-based policy framework can encourage more anticipatory, integrated, and sustainable disaster management governance, and provides important implications for the formulation of public policy at the regional level.